Organisation and implementation of public control over activities related to the provision of psychiatric care: current problems and development prospects - Goncharov, Vitaly V. (Journal of the Belarusian State University. Law, 2022)
This article is devoted to the analysis of modern problems associated with the organisation and implementation of public control over activities related to the provision of psychiatric care in the Russian Federation, as well as the development of a system of measures to resolve them in order to develop this institution of civil society. The purpose of the resеarch is, firstly, to study the main subjective and objective problems that hinder the effective organisation and implementation of public control over activities related to the provision of psychiatric care, as well as the reasons that give rise to them, and secondly, to develop and substantiate a system of measures for their solution. The object of the research is public relations in the field of organisation and implementation of public control in Russia over activities related to the provision of psychiatric care. The subject of the research is the norms of Russian legislation on public control over activities related to the provision of psychiatric care, as well as the constitutional and legal doctrine in the field of the formation and functioning of the institution of public control. The author substantiates the position that in the Russian Federation a situation was developed when activities related to the provision of psychiatric care are not properly monitored by civil society, which is due, on the one hand, to the lack of the necessary legislative framework, and on the other hand, to the hypertrophied exaggerated role of public associations of psychiatrists in this matter. The author developed and substantiated a system of measures to resolve problems in the organisation and implementation of public control over activities related to the provision of psychiatric care, including proposals to optimise the current legislation both in the field of public control and in the field of regulation of the provision of medical services.